DIGITAL CUSTOMER ENGAGEMENT AND OMNICHANNEL CAPABILITY IN MSMEs: A CONCEPTUAL FRAMEWORK FOR CUSTOMER VALUE AND BUSINESS RESILIENCE - Anggun Yolistina; Nida Garnida Fitrianti (Organisasi Kreatif Indonesia Emas, 2024)
Abstract Background: Digital Customer Engagement And Omnichannel Capability In Msmes is increasingly relevant to MSMEs because competitive adaptation depends on the ability to combine limited internal resources with market knowledge, relationships, and disciplined organizational learning. Aims: This article develops an integrative conceptual framework for digital customer engagement and omnichannel capability in msmes and explains its contribution to MSME competitiveness and resilience. Research Method: The study uses an integrative conceptual review of established scholarly literature available before the July 2024 issue placement. No primary survey, interview, experiment, or statistical dataset is claimed. Results and Conclusion: The synthesis identifies connected managerial capabilities involving sensing, knowledge acquisition, coordination, experimentation, implementation, evaluation, and learning. The framework emphasizes that sustainable outcomes depend on strategic fit, stakeholder trust, resource discipline, and repeated adaptation. Contribution: The paper provides a structured framework, practical indicators, and propositions that can guide future empirical research and MSME development programs.